BANK-SPECIFIC AND MACROECONOMIC DETERMINANTS OF NON-PERFORMING LOANS OF COMMERCIAL BANKS IN BANGLADESH - Towhid, ASM; Shinta Amalina Hazrati Havidz; Mohammed Ameen Qasem Ahmed Alnawah (Dinasti International Journal of Management Science, 2019)
The prime objective of this research is to identify the main determinants of non-performing loans in the commercial banking system of Bangladesh for the period 2011-2016 using panel data modeling. This paper uses balanced panel data method to examine both bank-specific (return on average assets, net loans to deposit ratio, bank size, cost-to-income ratio, and capital adequacy ratio) and macroeconomic (real GDP growth rate and inflation rate) variables. To attain the objectives, the present research analyzed historical data and panel data model using secondary data. To examine panel data modeling, the researcher considers 16 private commercial banks in Bangladesh and executed pooled OLS model, fixed effect model, random effect model and random effect with the robust standard error. The researcher found a negative significant relationship for return on average assets, net loans to deposit ratio and inflation rate in relation to NPLs and results are supporting the previous researcher. Based on the findings, the study offers some valuable strategies to the management to improve return on average assets, net loans to deposit ratio and inflation rate to reduce the NPLs at least under the tolerance level. The study also delineates the limitations of this work and direction for future research.